A novel role for inhibitor of apoptosis (IAP) proteins as regulators of endothelial barrier function by mediating RhoA activation. Issue 4 (26th December 2013) - Hornburger, Michael C.; Mayer, Bettina A.; Leonhardt, Stefanie; Willer, Elisabeth A.; Zahler, Stefan; Beyerle, Andrea; Rajalingam, Krishnaraj; Vollmar, Angelika M.; Fürst, Robert
Abstract : Inhibitor of apoptosis (IAP) proteins, such as XIAP or cIAP1/2, are important regulators of apoptosis in cancer cells, and IAP antagonists are currently evaluated as antitumor agents. Beyond their function in cancer cells, this study demonstrates a novel role of IAPs as regulators of vascular endothelial permeability. Two structurally different IAP antagonists, ABT and Smac085, as well as silencing of IAPs, reduced the thrombin receptor‐activating peptide (TRAP)‐induced barrier dysfunction in human endothelial cells as assessed by measuring macromolecular permeability or transendothelial electrical resistance. ABT diminished thrombin‐evoked stress fiber formation, activation of myosin light chain 2, and disassembly of adherens junctions independent of calcium signaling, protein kinase C, and mitogen‐activated protein kinases. Interestingly, ABT and silencing of IAPs, in particular XIAP, reduced the TRAP‐evoked RhoA activation, whereas Rac1 was not affected. XIAP and, to a lesser extent, cIAP1 were found to directly interact with RhoA independently of the RhoA activation status. Under cell‐free conditions, XIAP did not induce an ubiquitination of RhoA. In summary, our work discloses IAPs as crucial regulators of endothelial permeability and suggests IAP inhibition as interesting approach for the prevention of endothelial barrier dysfunction.—Hornburger, M. C., Mayer, B. A., Leonhardt, S., Willer, E. A., Zahler, S., Beyerle, A., Rajalingam, K., Vollmar, A. M., Fürst, R. A novel role for inhibitor of apoptosis (IAP) proteins as regulators of endothelial barrier function by mediating RhoA activation. FASEB J. 28, 1938–1946 (2014). www.fasebj.org